2014
DOI: 10.1088/0004-637x/782/2/95
|View full text |Cite
|
Sign up to set email alerts
|

The Chemical Imprint of Silicate Dust on the Most Metal-Poor Stars

Abstract: We investigate the impact of dust-induced gas fragmentation on the formation of the first lowmass, metal-poor stars (< 1M ) in the early universe. Previous work has shown the existence of a critical dust-to-gas ratio, below which dust thermal cooling cannot cause gas fragmentation. Assuming the first dust is silicon-based, we compute critical dust-to-gas ratios and associated critical silicon abundances ([Si/H] crit ). At the density and temperature associated with protostellar disks, we find that a standard M… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
89
2

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(92 citation statements)
references
References 104 publications
(232 reference statements)
1
89
2
Order By: Relevance
“…This was also shown by Ji et al (2014) within a simple onezone framework. Schneider et al (2012b) postulated that to have fragmentation at the metallicity of Caffau's star f dep should be larger than 0.01.…”
Section: Grain Size Distributionssupporting
confidence: 66%
“…This was also shown by Ji et al (2014) within a simple onezone framework. Schneider et al (2012b) postulated that to have fragmentation at the metallicity of Caffau's star f dep should be larger than 0.01.…”
Section: Grain Size Distributionssupporting
confidence: 66%
“…Hence, there should be a threshold value (D trans = −3.5) below which C and O fine-structure line cooling would not be able to drive low-mass star formation ("Forbidden Zone"-see also Frebel et al (2007b). Ji et al (2013) consider an alternative fragmentation mode, the impact of thermal cooling from silicon-based dust on the formation of low-mass stars in the early universe. This channel could account for the formation of low-mass EMP stars in cases where an insufficient amount of C and O were present to induce fragmentation of the gas cloud.…”
Section: The "Forbidden Zone" and Available Fragmentation Scenariosmentioning
confidence: 99%
“…The lower panel of Figure 8 shows the behavior of the [Si/H] abundance as a function of the metallicity for the program stars and stars from the literature. The solid line represents [Si/Fe] = 0, and the shaded areas show the lower limits on the Si abundances that would allow fragmentation (see Figure 5 of Ji et al 2013 for further details on the models). One can see that our program stars, as well as the stars from Cayrel et al (2004) and Yong et al (2013a), lie above the limits using both criteria, so their formation can be explained by either one of these processes.…”
Section: The "Forbidden Zone" and Available Fragmentation Scenariosmentioning
confidence: 99%
“…Simplified theoretical models (Frebel et al 2007;Safranek-Shrader et al 2010;Ji et al 2014) suggested possible conditions to form low mass CEMP stars that can be observed today by evaluating the amount of metals needed to induce cooling and subsequent fragmentation. Salvadori et al (2007Salvadori et al ( , 2010 explored the metallicity distribution function to probe the stellar population history of the Milky Way providing a critical metallicity of Z crit /Z ⊙ = 10 −4 .…”
Section: Introductionmentioning
confidence: 99%